Decolonising the archives: languages as enablers and barriers to accessing public archives in South Africa - Isabel S. Schellnack-Kelly (Archives & Manuscripts, 2020)
Under a democratic dispensation in South Africa, which recognises eleven official languages, language is still used to divide and segregate people and different cultures. The examples of how languages have divided South Africa from colonial times to the current dispensation are evident in archival collections housed by the country’s public archives services. A qualitative study was undertaken to identify all the languages of the different archival collections held by the public archives services in South Africa. Utilising a postmodernist ontology, this paper investigates the challenges pertaining to the large volumes of collections where access is restricted due to language barriers with limited assistance to provide translation services.